Comparison of Joint and Muscle Biomechanics in Maximal Flywheel Squat and Leg Press - Sjöberg, Maria; Berg, Hans E.; Norrbrand, Lena; Andersen, Michael S.; Gutierrez-Farewik, Elena M.; Sundblad, Patrik; Eiken, Ola (Frontiers in Sports and Active Living, 2021)
The aim was to compare the musculoskeletal load distribution and muscle activity in two types of maximal flywheel leg-extension resistance exercises: horizontal leg press, during which the entire load is external, and squat, during which part of the load comprises the body weight. Nine healthy adult habitually strength-training individuals were investigated. Motion analysis and inverse dynamics-based musculoskeletal modelling were used to compute joint loads, muscle forces, and muscle activities. Total exercise load (resultant ground reaction force; rGRF) and the knee-extension net joint moment (NJM) were slightly and considerably greater, respectively, in squat than in leg press (p ≤ 0.04), whereas the hip-extension NJM was moderately greater in leg press than in squat (p = 0.03). Leg press was performed at 11° deeper knee-flexion angle than squat (p = 0.01). Quadriceps muscle activity was similar in squat and leg press. Both exercise modalities showed slightly to moderately greater force in the vastii muscles during the eccentric than concentric phase of a repetition (p ≤ 0.05), indicating eccentric overload. That the quadriceps muscle activity was similar in squat and leg press, while rGRF and NJM about the knee were greater in squat than leg press, may, together with the finding of a propensity to perform leg press at deeper knee angle than squat, suggest that leg press is the preferable leg-extension resistance exercise, both from a training efficacy and injury risk perspective.